Writing through music : essay on music, culture, and politics - Pasler, Jann (Oxford University Press, 2008)
List of Illustrations. List of Musical Examples. Introduction. I. Time, Narrative, and Memory. 1. Narrative and Narrativity in Music. 2. Postmodernism, Narrativity, and the Art of Memory. 3. Resituating the Spectral Revolution: French Antecedents. II. Self-Fashioning. 4. Deconstructing d'Indy, or the Problem of a Composer's Reputation. 5. New Music as Confrontation: the Musical Sources of Cocteau's Identity. 6. Inventing a tradition: John Cage's Composition in Retrospect. III. Identity and Nation. 7. Pelleas and Power: Forces behind the Reception of Debussy's Opera. 8. The Ironies of Gender, o.